2008
DOI: 10.1002/hep.22149
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plasma membrane autoantigens in autoimmune hepatitis type 1 using a proteomics tool

Abstract: Autoimmune hepatitis (AIH) is a liver disease with circulating autoantibodies predominantly directed against widely held cellular components. Because AIH is a liver-specific disease, autoantibodies against plasma membrane antigens may be involved in its pathogenesis and have been reported; however, no definite identification has been described. We thus investigated the fine specificity of anti-hepatocyte plasma membrane autoantibodies in type 1 AIH (AIH-1) using a proteomic tool. A plasma membrane-enriched fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 48 publications
0
27
0
1
Order By: Relevance
“…Proteomics studies have suggested that p97/VCP might play some role in the liver regeneration and in fetal liver development (31), and it has also been shown that p97/VCP contributes to the formation of Mallory bodies (32). Moreover, p97/VCP autoantibodies have been found in cases of autoimmune hepatitis (33), primary biliary cirrhosis (34,35), and in HCC (36). Elevated expression of p97/VCP in HCC has also been associated with increased incidence of tumor recurrence (37).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics studies have suggested that p97/VCP might play some role in the liver regeneration and in fetal liver development (31), and it has also been shown that p97/VCP contributes to the formation of Mallory bodies (32). Moreover, p97/VCP autoantibodies have been found in cases of autoimmune hepatitis (33), primary biliary cirrhosis (34,35), and in HCC (36). Elevated expression of p97/VCP in HCC has also been associated with increased incidence of tumor recurrence (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the emergence of protein microarray technology is expanding the repertoire of autoantigens that might prove useful in understanding the immunological targets of autoimmune hepatitis and improving its diagnosis [136,137]. Six plasma membrane autoantigens have been implicated in type 1 autoimmune hepatitis, including liver arginase, cytokeratins, heat-shock proteins, and valosin-containing protein [138]. The interleukin-4 receptor (CD124) has high individual sensitivity and specificity for autoimmune hepatitis, and it generates functional autoantibodies that neutralize interleukin-4 [139].…”
Section: Insights Into the Principal Target Autoantigen Of Autoimmunementioning
confidence: 99%
“…In addition, liver cell membrane preparations have been repeatedly studied by analytical biochemistry, but none of the identified reactants have attained candidate status as a liver-specific or disease-specific autoantigen. The latest and most detailed of the studies [70] disclosed several reactive components that were molecularly identified as likely constituents of the liver membrane (liver arginase, cytokeratins, heat shock proteins, and valosincontaining protein), but, as in previous studies, these components reacted weakly with normal sera (i.e., with natural antibodies), apparently becoming 'amplified' in the course of hepatocellular destruction. Thus, is the explanation for their appearance in AIH a 'destruction-dependent' amplification of natural reactivity, and might this be integral to pathogenetic processes in liver autoimmunity?…”
Section: Diagnostic Criteria For Aih: Simplified and 'Super-simplified'mentioning
confidence: 89%